Knowledge management with a web platform on training offer and job demand in the professional interest of young people from a CETPRO - Luque Ticona, Dikxon Angel (2023)
In the last five years, important attention was given to the creation of knowledge to share and apply it for the good of organizations, generating information and with the help of technologies, the management of their knowledge is directed. An interesting experience was carried out by collecting key data available to various state institutions, generating relevant information organized and systematized in a web platform for the knowledge of young people or the general public in decision-making regarding their professional interest. In 2015, the platform "Ponte en carrera" was launched, which helps young people whose information available up to that moment was limited and even empirical, and that this platform presents information for knowledge about professional careers, investment, and more details about higher education in their various training offers, combined with information from the labor market, such as the remunerative income of the professionals formally declared, giving an idea about the returns of the training, constituting a significant contribution in the vocational guidance service from the state. In this study we check if the web platform supports the knowledge management of a group of young people from a Technical Productive Educational Center, about their professional interest.